HALVING OF MORTALITY OF SEVERE MELIOIDOSIS BY CEFTAZIDIME - N. J. White (2018)
An open randomised trial was conducted to compare ceftazidime (120 mg/kg/day) with "conventional therapy" (chloramphenicol 100 mg/kg/day, doxycycline 4 mg/kg/day, trimethoprim 10 mg/kg/day, and sulphamethoxazole 50 mg/kg/day) in the treatment of severe melioidosis. A paired restricted sequential trial designed to detect a reduction in mortality from 80 to 40% in culture-positive patients surviving > 48 hours was stopped after 22 months. Of the 161 patients entered into the study, 65 had bacteriologically confirmed melioidosis and 54 of these were septicaemic. Ceftazidime treatment was associated with a 50% (95% CI 19-81%) lower overall mortality than conventional treatment (74% vs 37%; p=0·009) and should now become the treatment of choice for severe melioidosis. © 1989.